Educação em saúde realizada por profissionais da saúde à familiares de crianças com paralisia cerebral - Nagliate, Patrícia de Carvalho (Universidade Federal de São Carlos, 2009)
In the health promotion context, health education is very important and indispensable in the health professional practice. The health education still needs improvement in its applicability, in order to provide better quality of life and health of individuals with Cerebral Palsy (CP). The CP is a permanent movement and posture disorder, due to a non-progressive brain lesion at the life beginning, which promotes several driven dysfunctions, causing limitations in the movements and daily living activities. Therefore, the health professional has to promote understanding of the health-care and disease, through health education to the families of these children. There is a lack of relevant literature about how is being done the health education process to the families. The purpose of this work was to identify how the health professionals are practicing the health education process to the CP child family. The study was conducted at institutions that serve children with CP, the samples were 07 health professionals and 07 CP child relatives that living in a country city of São Paulo Brazil. Data collection was conducted through semi-structured interviews and observation. Semi-structured interviews were conducted with family members and professionals, with the aim of obtaining information about how the health education process is being conducted from the participants point of view. Also, it was carried out systematic observation of the two professional action during the interaction between two CP child families while the care was conducted. Being an exploratory descriptive study based on the qualitative referential was possible, through the transcript of the interviews and simplified analysis of the results contents, with the professionals analysis to get five themes: 1. Relationship; 2. Institution; 3. Professional s routine in the CP children serve; 4. Teach methodology; 5. Health education with the categories and two sub-categories. And with the familiar analysis, two themes: 1. Understanding the cerebral palsy and; 2. How the parents facing up to cerebral palsy children care, with yours categories. With the results it was concluded that the health education practice are realized, but it still has mistakes. This happen because it is a complex situation that involve the participants world making the perfect practice execution difficult. Therefore, the mentioned subject matter could offer important contributions to make a better health professional aware in the moment and form to approach and to mix with CP s familiar. So, this will promote a confidence relation and the continuity of health education practice at home with the purpose to reach a better quality of life for this children and the parents.
Health education carried out by the health professionals to the family of children with cerebral palsy
Keywords: Educação e saúde; Educação especial; Profissionais da saúde; Crianças deficientes - relações familiares; Paralisia cerebral; Cerebral palsy; Family; Health education; Health professionals; Special education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL